Long-term evolution of the S788 fungal nuclear small subunit rRNA group I introns - HAUGEN, PEIK (Copyright 2004 by RNA Society, 2004)
More than 1000 group I introns have been identified in fungal rDNA. Little is known, however, of the splicing and secondary structure evolution of these ribozymes. Here, we use a combination of comparative and biochemical methods to address the evolution and splicing of a vertically inherited group I intron found at position 788 in the fungal small subunit (S) rRNA. The ancestral state of the S788 intron contains a highly conserved core and an extended P5 domain typical of IC1 introns. In contrast, the more derived introns have lost most of P5, and have an accelerated divergence rate within the core region with three functionally important substitutions that unambiguously separate them from the ancestral pool. Of 14 S788 group I introns that were tested for splicing, five, all of the ancestral type, were able to self-splice and produced intron RNA circles in vitro. The more derived S788 introns did not self-splice, and potentially rely on fungal-specific factors to facilitate splicing. In summary, we demonstrate one possible fate of vertically inherited group I introns, the loss of secondary structure elements, lessened selective constraints in the intron core, and ultimately, dependence on host-mediated splicing.